Pyrolysis of furfural residues: Property and applications of the biochar. (15th August 2022) - Inkoua, Stelgen; Li, Chao; Fan, Huailin; Bkangmo Kontchouo, Félix Mérimé; Sun, Yifan; Zhang, Shu; Hu, Xun
Abstract: Furfural residue (FR) is a solid waste generated during the production of furfural from corn cobs. The chemical energy and material potential of FR can be potentially recovered via pyrolysis. In this study, the pyrolysis of FR at the temperature ranging from 350 to 650 °C at the varied heating rate was investigated, aiming to understand the characteristics of the pyrolysis products. The results indicate that the organic components of FR tend to be cracked to form biochar and gases as the dominate products, due to the high ash content of FR. The FR-derived bio-oil also contained abundant organics derived from cellulose and lignin. Increasing pyrolysis temperature favored formation of the organics with fused ring structures. Lower heating rate in pyrolysis also formed biochar with higher thermal stability and higher fixed carbon content by enhancing the extent of deoxygenation. Additionally, the transformation of –OH via dehydration, -C-H into = C–H via dehydrogenation, and the cracking of CO during carbonization of biochar in the pyrolysis were also observed during pyrolysis of FR. Activation of the FR-derived biochar generated abundant micropores and mesopores, rendering the activated carbon with superior specific capacitance as electrodes of electrocapacitors (329 Fg -1 ) and the excellent adsorption efficiency of phosphate (up to 98.81%). Highlights: Property of biochar from pyrolysis of furfural residues is studied. High ash content in FR promoted gasification of volatiles, producing less bio-oil. Lower heating rate enhanced thermal stability and fixed carbon content of biochar. Activation of biochar from slow pyrolysis produces abundant micropores. Activated carbon shows superior performance as electrodes or for adsorption.